AMPK and Pulmonary Hypertension: Crossroads Between Vasoconstriction and Vascular Remodeling - Zhao, Qiang; Song, Ping; Zou, Ming-Hui (Frontiers in Cell and Developmental Biology, 2021)
Pulmonary hypertension (PH) is a debilitating and life-threatening disease characterized by increased blood pressure within the pulmonary arteries. Adenosine monophosphate-activated protein kinase (AMPK) is a heterotrimeric serine-threonine kinase that contributes to the regulation of metabolic and redox signaling pathways. It has key roles in the regulation of cell survival and proliferation. The role of AMPK in PH is controversial because both inhibition and activation of AMPK are preventive for development of PH. Some clinical studies found that metformin, the first-line antidiabetic drug and the canonical AMPK activator, has therapeutic efficacy during treatment of early-stage PH. Other study findings suggest the use of metformin is preferentially beneficial for treatment of PH associated with heart failure with preserved ejection fraction (PH-HFpEF). Therefore, the pulmonary vascular effects of metformin might be less pronounced than the effects on the right ventricle. In this review, we discuss the “AMPK paradox” and highlight the differential effects of AMPK on pulmonary vasoconstriction and pulmonary vascular remodeling. We also review the effects of AMPK activators and inhibitors for rescue of preexisting PH in animals and include a discussion of gender differences in the response to metformin in PH.